Cognitive vulnerability factors in depression pancultural or culture-specific? - Reyes, Jose Alberto S. (2005)
This study examined whether the salience of the cognitive vulnerability factors in depression is universal or mediated by culture. Students from the Philippines, Japan, and Canada participated in this study. Results showed that there across the three student groups, there are different models that could account for the role played by cognitive vulnerability factors in the prediction of depression. The implications of the findings on the manner in which depression is conceptualize day in Non-Western cultures is discussed.
Keywords: Depression, Mental